2020
DOI: 10.1155/2020/1980921
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes and miRNAs Associated with Esophageal Squamous Cell Carcinoma by Integrated Analysis of Microarray Data

Abstract: To identify candidate key genes and miRNAs associated with esophageal squamous cell carcinoma (ESCC) development and prognosis, the gene expression profiles and miRNA microarray data including GSE20347, GSE38129, GSE23400, and GSE55856 were downloaded from the Gene Expression Omnibus (GEO) database. Clinical and survival data were retrieved from The Cancer Genome Atlas (TCGA). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of differentially expressed genes (DEGs) was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…In addition to everything described so far related to miRNA-155-5p, that miRNA and miRNA-1248, which is associated with good survival prognoses in cancer (38), both upregulated on EARLY treated HIV-1 patients, strongly correlated with the activation marker HLA-DR, the natural cytotoxicity family activation receptor NKp30 and the inhibiting receptor NKG2A expressed on NK cells and more specifically on the main cytotoxic NK subset, CD16 high and the activated and mature CD56 neg CD16+ NK cells, described as a subset with impaired effector functions in HIV-1 infection (39). Despite the limitation that miRNA profile was determined in the pool of PBMCs without isolated different cell subsets, our results are in agreement with recent insights that have highlighted the role of miRNAs in maintaining killing effect of NK cells in cancer scenario via activation markers modulation (40)(41)(42), in promoting antiviral immunity in the scenario of viral infection (43) and altogether suggests the possible role of both, miRNA-155-5p and miRNA-1248 in regulating inflammatory cytokine production in NK cells, potentially balancing disease progression during chronic HIV infection.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to everything described so far related to miRNA-155-5p, that miRNA and miRNA-1248, which is associated with good survival prognoses in cancer (38), both upregulated on EARLY treated HIV-1 patients, strongly correlated with the activation marker HLA-DR, the natural cytotoxicity family activation receptor NKp30 and the inhibiting receptor NKG2A expressed on NK cells and more specifically on the main cytotoxic NK subset, CD16 high and the activated and mature CD56 neg CD16+ NK cells, described as a subset with impaired effector functions in HIV-1 infection (39). Despite the limitation that miRNA profile was determined in the pool of PBMCs without isolated different cell subsets, our results are in agreement with recent insights that have highlighted the role of miRNAs in maintaining killing effect of NK cells in cancer scenario via activation markers modulation (40)(41)(42), in promoting antiviral immunity in the scenario of viral infection (43) and altogether suggests the possible role of both, miRNA-155-5p and miRNA-1248 in regulating inflammatory cytokine production in NK cells, potentially balancing disease progression during chronic HIV infection.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, miR-1248 has also been suggested as a prognostic biomarker in patients with Wilms tumour and ESCC [59,60], conversely its role as prognostic biomarkers for progressive supratentorial hemispheric pLGGs emerges for the first time in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, a wider study of the literature showed that miR-1248 has already been described as an oncomiR correlated with cancer progression in tumours of different tissue-origin [53][54][55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…The “Search Tool for the Retrieval of Interacting Genes” (STRING) database (version: 11.5) was used to construct a PPI network to comprehend interactions between the DEGs with medium confidence of 0.400 and 5% FDR stringency based on text mining, experiments, databases, and co‐expression which were limited to “Homo sapiens” (Karimizadeh et al, 2019; Zhang et al, 2020). The following network was exported to Cytoscape to find important nodes using the Molecular Complex Detection (MCODE) clustering algorithm and cytoHubba plugin to identify hub genes based on the topological algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…Micro RNAs (miRNAs) are short read, non-coding RNAs (19-25 nucleotides) associated in several pathways via regulatory network control and subsequently involved in gene expression by forming miRNA-mRNA duplex leading to mRNA degradation (O'Brien et al, 2018;Zhang et al, 2019). miRNA can regulate cellular processes involved in the development of tissue and organs, namely cell differentiation, proliferation, and death (Yao, 2016). Due to this level of involvement, any dysregulation of miRNA-mRNA networks can lead to the onset and progression of human diseases (Dong et al, 2020).…”
mentioning
confidence: 99%